Design, analysis and fabrication of shoe dryer / Muhammad Akmal Hazim Abdul Halim - Abdul Halim, Muhammad Akmal Hazim (2022)
Drying shoes under the sun may take quite a long time for the shoes to dry and may depend on the weather. As a solution to this problem, a shoe dryer is designed. This shoe dryer is easy to carry anywhere and take a short drying time. The air source uses the concept of a hair dryer mechanism where air is generated from the rotation of the fan driven by an electric source and heats the air heater at a low level of this design is to make it easy for people to dry their shoes. With the design of this shoe dryer that is light and easy to carry and to some extent provide the convenience to dry shoes anywhere. This shoe dryer was produced cheap and using durable materials so that it is affordable tool. The shoe dryer is mobile and easy to carry because the size was designed medium sized tool. Then, Shoe Dryer 2.0 is designed to overcome these problems.